WRITTEN LAW IN THE LEGISLATION SYSTEM: A LITERATURE REVIEW OF THE CONCEPT, FUNCTION, AND ROLE IN ENSURING LEGAL CERTAINTY - Gunawan Widjaja (Adisam Publisher, 2025)
This study aims to comprehensively examine the concept, function, and role of written law in the Indonesian legal system, particularly in ensuring legal certainty. Using a literature review method and a qualitative-descriptive approach, this study explores various sources of literature, ranging from legal doctrine, legislation, to previous research results. The results of the study show that written law has regulatory, instrumental, and legitimising functions, as well as a strategic role as a main pillar in a state based on the rule of law that guarantees legal certainty for all citizens. However, challenges such as overlapping regulations, unclear formulation of norms, and weak harmonisation of regulations remain obstacles to optimising the role of written law. Therefore, efforts to improve the drafting, harmonisation, dissemination, and enforcement of written law are crucial to strengthening the guarantee of legal certainty in Indonesia.